Tele-Assessment of Core Performance and Functional Capacity: Reliability, Validity, and Feasibility in Healthy Individuals - Gungor, Feray; Ovacik, Ugur; Harputlu, Ozge Ertan; Yekdaneh, Ayse Asena; Kurt, Irem; Uzunoglu, Gamze Erturk; Akbaba, Yildiz Analay; Ertürk Uzunoğlu, Gamze; Ertan Harputlu, Özge (Sage Publications Ltd, 2024)
Introduction Many assessment methods are used in physiotherapy to analyze the fitness level and injury risk in athletes, and to determine the general health status and the effectiveness of the treatment applied in patients. Considering the need for telehealth use, it is essential to determine the usability of tests performed as tele-assessment. This study aimed to examine the intra-rater reliability, validity, and feasibility of the tele-assessment version of core strength and endurance and functional capacity assessments in healthy individuals. Methods "Curl-up," "Modified Push-up," "Plank," and "Lateral Bridge" tests were used for core strength and endurance performance assessment, and "Timed Up and Go," "30 second Sit to Stand," and "Functional Reach Test" tests were used for functional capacity assessment in healthy individuals. Participants were evaluated first by tele-assessment, then one hour later on the same day, all assessments were repeated face-to-face procedures by the researchers thus the validity of the tele-assessment method was determined. All tests were applied as tele-assessment one week later to determine the intra-rater reliability of the tele-assessment method. The system usability scale was applied to evaluate the usability of our tele-assessment method. Results Eighty healthy people were enrolled. Intraclass correlation coefficients ranged between 0.91 and 0.97 for core performance tests and between 0.95 and 0.97 for functional tests. All tele-assessment versions of the core performance and functional tests were highly correlated with the face-to-face versions. Discussion Core strength-endurance and functional tests performed via tele-assessment were reliable, valid, and feasible for practically measuring the performance of healthy young adults. This study supports the tele-assessment versions of these tests.
Polat Ilguz, Basak/0000-0003-1072-4128; Ovacik, Ugur/0000-0001-6137-3466; Gungor, Feray/0000-0003-2814-3276; ANALAY, YILDIZ/0000-0002-8141-6977
Keywords: Tele-Assessment; Trunk Performance; Physical Capacity; Telehealth; Intra-Rater Reliability; Validity; Feasibility; Telerehabilitation; Physiotherapy